Case report: Block recession calcaneoplasty of the calcaneal tuber for treating lateral superficial digital flexor tendon luxation in a dog - Nam, Sanghyun; Lee, Haebeom; Roh, Yoonho; Kang, AhRan; Kim, Daehyun; Jeong, Seongmok; Jeong, Jaemin (Frontiers in Veterinary Science, 2022)
A 4-year-old, intact, female, Collie was presented with 5 month history of right hindlimb lameness. Lateral luxation of the superficial digital flexor tendon (SDFT) was diagnosed on the basis of the clinical, radiographic and ultrasonographic finding. Intraoperatively, shallow right calcaneal tuber was observed. Block recession calcaneoplasty with retinaculum repair using anchor screw were performed to manage SDFT luxation. Additionally, temporary restraining pin was placed on lateral aspect of the calcaneal tuber. The patient demonstrated mild lameness at 2 weeks postoperatively and improved to normal limb function at 12 weeks postoperatively. As the gold standard of surgical techniques for SDFT luxation has not yet been reported, block recession calcaneooplasty may be an alternative surgical option for patients with calcaneal morphologic abnormalities causing SDFT luxation.